2023
DOI: 10.1038/s41586-023-05738-w
|View full text |Cite
|
Sign up to set email alerts
|

Ageing threatens sustainability of smallholder farming in China

Abstract: Rapidly demographic aging substantially affects socioeconomic development [1][2][3][4] , presents grand challenges for food security and agricultural sustainability [5][6][7][8] , which have so far not been well understood. Here, by using over 30,000 households survey across China, we show that rural population aging lowers average education level of farmers by 3% (0-11% across different provinces) and reduces farm size by 4% (2-11%) due to land transfer-out and abandonment in 2019. These changes further led t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 57 publications
1
12
0
2
Order By: Relevance
“…However, with rapid urbanization, economic development and successful industrialization, the shifting of the economy from agriculture to nonagricultural sectors in China and India has proved advantageous. In addition, the global population is ageing at an increasing rate 20 , which could also lead to labor shortages on small farms. A comprehensive transformation of smallholder farming to a more sustainable agriculture is urgently needed to overcome the ageing of the rural population in developing countries, especially in China and India.…”
Section: Discussionmentioning
confidence: 99%
“…However, with rapid urbanization, economic development and successful industrialization, the shifting of the economy from agriculture to nonagricultural sectors in China and India has proved advantageous. In addition, the global population is ageing at an increasing rate 20 , which could also lead to labor shortages on small farms. A comprehensive transformation of smallholder farming to a more sustainable agriculture is urgently needed to overcome the ageing of the rural population in developing countries, especially in China and India.…”
Section: Discussionmentioning
confidence: 99%
“…Agriculture was mainly operated by the remaining older men or women, which may lead to poor management of cropland resources (Jin et al, 2021). A recent study showed that rural population ageing threatens the sustainability of smallholder farming in China through cropland ownership transfers and land abandonment (Ren et al, 2023). To mitigate this issue, policy regulation is needed through the Land Transfer System or reform of the land tenure system.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al [ 33 ] suggest that building trust, participatory innovation, developing human capacity, and strengthening the coherence of farming communities play a crucial role in the sustainability of agriculture. Moreover, Ren et al [ 34 ] find that rapid population ageing leads to increased fertilizer losses and exacerbates the release of environmental pollutants, and that the management of rural ageing will contribute to the overall transition of smallholder farmers to sustainable agriculture in China. Wang et al [ 35 ] suggest that an integrated knowledge and product strategy (IKPS) approach can improve food security while reducing resource and environmental burdens, and Duan et al [ 36 ] find that the integration of agricultural land can contribute to sustainable agricultural development in China.…”
Section: Literature Reviewmentioning
confidence: 99%